Leptothrix cholodnii Response to Nutrient Limitation - Kunoh, Tatsuki; Yamamoto, Tatsuya; Sugimoto, Shinya; Ono, Erika; Nomura, Nobuhiko; Utada, Andrew S. (Frontiers in Microbiology, 2021)
Microorganisms are widely utilized for the treatment of wastewater in activated sludge systems. However, the uncontrolled growth of filamentous bacteria leads to bulking and adversely affects wastewater treatment efficiency. To clarify the nutrient requirements for filament formation, we track the growth of a filamentous bacterium, Leptothrix cholodnii SP-6 in different nutrient-limited conditions using a high aspect-ratio microfluidic chamber to follow cell-chain elongation and sheath formation. We find that limitations in Na+, K+, and Fe2+ yield no observable changes in the elongation of cell chains and sheath formation, whereas limitations of C, N, P, or vitamins lead to more pronounced changes in filament morphology; here we observe the appearance of partially empty filaments with wide intercellular gaps. We observe more dramatic differences when SP-6 cells are transferred to media lacking Mg2+ and Ca2+. Loss of Mg2+ results in cell autolysis, while removal of Ca2+ results in the catastrophic disintegration of the filaments. By simultaneously limiting both carbon and Ca2+ sources, we are able to stimulate planktonic cell generation. These findings paint a detailed picture of the ecophysiology of Leptothrix, which may lead to improved control over the unchecked growth of deleterious filamentous bacteria in water purification systems.